Humdiana, PERANCANGAN BUSINESS CONTINUITY PLAN : STUDI KASUS PADA PT.PAM - Humdiana Roelly S.Kom., MM., M.Kom (Institut Bisnis dan Informatika Kwik Kian Gie, 2012)
Business Continuity Plan is needed to complement and strengthen the system so that a reliable system. Indonesia is a disaster prone areas are less aware of the business principals to the disaster. BCP using Sharing Vision Framework to produce a form of design that suits your needs and business processes with case studies PT.PAM company that operates in the automotive industry, workshop and body repair services specialist. Sharing Vision Framework methodology starting from the identification of business processes, identify conditions and determination of IT Risk Assessment of risk and analysis that will produce the matrix for the next Risk Assessment and then carried to the process of collecting data in the Business Impact Assessment malalui questionnaires, interviews, or discussion by PT.PAM IT managers. Based on the results of Risk Assessment and Business Impact Assessment, then conducted the search and selection of alternative plans BCP strategy is the reference key in preparing a BCP document.Risk Assessment Results opportunity to explain the highest ranking threats to earthquake, fire, hacker attacks, BCP is not affected if there threats to strike and supplier failure. BIA results most business processes are at high and moderate categories, This shows every process in the service and Part Shop PT.PAM Workshop has a strong dependency relationship. Fifteen kinds of threats of disaster, the order of highest to lowest are: earthquakes, fires, hacker attacks, floods, bomb threats, software problems, hardware problems, problems of telecom, electricity supply problems, dangerous diseases / accidents, supplier failure, leaks B3, chaos , utility failure, and strike. Can in anticipation of the Strategy Plan are: Strategy Backup Hardware, Backup Strategy for electricity supply, Backup Strategy, Backup Strategy tekomunikasi channels, Backup Strategy of required supplies, personnel Backup Strategy, Site Recovery Strategy, Strategy Offsite libraries, escalation procedures and activation, and Insurance.